Reviewers' perceptions of the volume of information provided in environmental impact statements: The case for refocusing attention on what is relevant. (1st April 2020) - Fonseca, Alberto; Rivera Fernández, German Marino
Abstract: Environmental impact statements (EISs), the main source of information used by reviewers and decision-makers in the environmental impact assessment (EIA) process, are becoming increasingly lengthy. The implications of this phenomenon for decision-making have been mostly anecdotal. The objective of this article is twofold: first, it seeks to identify the main consequences of the growing volume of information provided in EISs for reviewing and decision-making; second, it aims at establishing how to better address the challenges of reviewing lengthy EISs. The perceptions of EIS reviewers were surveyed through an online questionnaire in Brazil. The 115 responses reveal that the growing volume of information provided in EISs has both positive and negative consequences. The majority of respondents perceived information needs to be context-dependent. Findings indicate that the challenges of reviewing lengthy EISs stem not so much from too much information, but rather from irrelevant information, as well as from weak capacity to process information. Therefore, enhancing the assessment scope and strengthening capacity-building are key steps in improving decision-making. The survey also revealed specific problems in Brazil's environmental agencies, such as lack of staff and agencies' growing dependence on information systems and repositories. The article highlights practical implications and suggests future avenues of research. Highlights: Reviewer perceptions of information volume in EISs were surveyed in Brazil. Most of the 115 respondents perceive information needs to be context-dependent. Better scoping and enhanced information-processing can improve EIS review Irrelevant information is more worrisome than too much information. Capacity-building is needed for both TR preparation and EIS review in Brazil.